Historical data on shallow-water invertebrates in Palu Bay, Indonesia to address the "Shifting Baselines" syndrome. Issue 1 (May 2021) - Ndobe, S; Gani, A; Salanggon, A M; Wahyudi, D; Rosyida, E; Moore, A M
Abstract: As global change accelerates in the Anthropocene, the "shifting baselines" paradigm is also exacerbated. In this context, it is important to make historical data available in order to assist in evaluating and mitigating the changes occurring. Even though data from the first two decades of the 21st Century do not represent a pristine or true baseline condition, it is important to collate and curate data from this period. Unfortunately, many data are unpublished or stored in temporary repositories for a short time horizon (e.g. 3-10 years) or in printed format only, greatly limiting detection and access. We present data from four studies on shallow water invertebrates in Palu Bay collected over the period from 2008 to 2010. The taxonomic groups covered are Molluscs (Gastropods), Echinoderms and Cnidaria (corals), with some data on other taxa. These data will be of especial interest as a reference in evaluating the condition and recovery of the coastal ecosystems of Palu Bay after the 2018 tsunami.